2001
DOI: 10.1054/bjoc.2001.1950
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the TGF β functional pathway in epithelial ovarian carcinoma

Abstract: Summary Epithelial ovarian carcinoma is often diagnosed at an advanced stage of disease and is the leading cause of death from gynaecological neoplasia. The genetic changes that occur during the development of this carcinoma are poorly understood. It has been proposed that IGFIIR, TGFβ1 and TGFβRII act as a functional unit in the TGFβ growth inhibitory pathway, and that somatic loss-of-function mutations in any one of these genes could lead to disruption of the pathway and subsequent loss of cell cycle control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 25 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…43 Somatic mutations of TbR-II are noticeable in hereditary nonpolyposis colorectal cancer, although these mutations are less frequent in most carcinomas without microsatellite instability. 14,15 Taken together, it seems likely that mutation of exon 3, 5, and 7 of TbR-II is a minor mechanism for TGF-b-resistance in ICC cells.…”
Section: Tgf-b1mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Somatic mutations of TbR-II are noticeable in hereditary nonpolyposis colorectal cancer, although these mutations are less frequent in most carcinomas without microsatellite instability. 14,15 Taken together, it seems likely that mutation of exon 3, 5, and 7 of TbR-II is a minor mechanism for TGF-b-resistance in ICC cells.…”
Section: Tgf-b1mentioning
confidence: 99%
“…Somatic mutations of TbR-II were firstly reported in some carcinoma cells, especially hereditary nonpolyposis colorectal cancer, 12,13 though the frequency was found to be relatively low in other carcinomas. 14,15 Other mechanisms of escaping tumor growth inhibition by TGF-b1 such as somatic mutation of Smads, transcriptional downregulation of TGF-b receptors, and overexpression of smad7, are also reported. [16][17][18][19] TGF-b1 is known to inhibit the proliferation of non-neoplastic epithelium at the G1/S phase via several cell cycle-related molecules such as cyclins (cyclins D, cyclin E), cdks (cdk2, cdk4, cdk6), and cdk inhibitors (p15, p21, p27).…”
mentioning
confidence: 99%
“…Although abnormalities in the expression or function of TGFß1 and its receptors, or molecules in the downstream signaling cascade, have been reported in several studies of ovarian cancer, some authors have reported significant abnormalities, while others have found minor changes and controversy exists (30)(31)(32)(33)(34). In addition, very few studies of ovarian cancer have assessed the associations between TGFß1 expression and the prognosis or sensitivity to anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a frameshift mutation has been identified in Exon 5 of TGFRI in 31% of ovarian tumors (Wang et al, 2000b), in exons 2, 3, 4, and 6 of TGFRI (catalytic domain of the kinase) in 33% primary ovarian cancers (Chen et al, 2001), and deletions in exon 1 of TGFRI in <30% of ovarian tumors (Antony et al, 2010). Likewise, missense mutations have been identified in TGFRII (Francis-Thickpenny et al, 2001) and deletions in exon 3 of TGFRII in ovarian tumors (Antony et al, 2010).…”
Section: Tgfreceptor Expression In Ovarian Cancermentioning
confidence: 99%